2014
DOI: 10.1186/1476-069x-13-95
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of the association between removal of dental amalgam, urine mercury and 14 self-reported health symptoms

Abstract: BackgroundMercury vapor poses a known health risk with no clearly established safe level of exposure. Consequently there is debate over whether the level of prolonged exposure to mercury vapor from dental amalgam fillings, combining approximately 50% mercury with other metals, is sufficiently high to represent a risk to health. The objective of our study is to determine if mercury exposure from amalgam fillings is associated with risk of adverse health effects.MethodsIn a large longitudinal non-blind sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 63 publications
5
6
0
Order By: Relevance
“…Since neither blinding nor placebo control was used, the observed reduction of the intensity of general health complaints can be interpreted as an effect from both specific and non-specific treatment effects. A reduction of health complaints is in agreement with data from previous controlled studies 22,23,26,30 and studies without comparison groups. 28,31 In cross-sectional studies of large cohorts, people with many amalgam fillings did not have more symptoms or diagnosed diseases than people with few fillings.…”
Section: Discussionsupporting
confidence: 91%
“…Since neither blinding nor placebo control was used, the observed reduction of the intensity of general health complaints can be interpreted as an effect from both specific and non-specific treatment effects. A reduction of health complaints is in agreement with data from previous controlled studies 22,23,26,30 and studies without comparison groups. 28,31 In cross-sectional studies of large cohorts, people with many amalgam fillings did not have more symptoms or diagnosed diseases than people with few fillings.…”
Section: Discussionsupporting
confidence: 91%
“…Different explanations, including patients' expectations , psychosocial treatment effects , elimination of worry , spontaneous recovery , and the natural course of the complaints , were suggested for the reported improvements in health. However, not all of the reported reductions were statistically significant, and the complaints that were statistically reduced varied from study to study (not described in Table 1, see for instance Zwicker et al, 2014). In the randomized controlled trial , clinically relevant reductions of health complaints were found for all interventions, including the one without amalgam removal.…”
Section: Norwaymentioning
confidence: 98%
“…The practitioners also provided an extensive list of complaints likely to be reported by amalgam patients . When investigating health complaints attributed to dental amalgam, some studies have relied on, and expanded on, questionnaires regarding common health complaints, such as the Giessener Symptom Complaints Checklist , whereas other studies have used self-constructed questionnaires with health complaints that the researchers, based on the existing research literature and their own clinical experience, believe are core symptoms reported by patients with health complaints attributed to dental amalgam Zwicker, Dutton, & Emery, 2014).…”
Section: Patients With Health Complaints Attributed To Dental Amalgammentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusion was deducted on the basis of results that removal of amalgam fillings reduced the self-reported symptom deterioration and increased the possibility of symptom improvement in comparison to people who retained their amalgam fillings. [ 6 ] In contrast, Nicolae et al . opined that mean urinary mercury concentrations in Canadian population are significantly lower than the values considered to pose any risks for health.…”
Section: Discussionmentioning
confidence: 99%